2016
DOI: 10.1186/s12874-016-0236-x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of adherence in a randomised controlled trial of a complex intervention: supported self-management for adults with learning disability and type 2 diabetes

Abstract: BackgroundReporting adherence to intervention delivery and uptake is a detailed way of describing what was actually delivered and received, in comparison to what was intended. Measuring and reporting adherence is not routinely done well in complex interventions. The OK Diabetes trial (ISRCTN41897033) aimed to develop and subsequently test the feasibility of implementing a supported self-management intervention in adults with a learning disability and type 2 diabetes. A key study objective was to develop a meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…This is particularly important for fidelity investigations. While the BCC fidelity framework provides a synthesised conceptualisation and definition of different fidelity dimensions, the authors themselves acknowledge that there is little standardised guidance on how to operationalise each dimension, and a consequent need for further empirical examples of how each dimension has been quantified and interpreted [14, 38]. It is thus hoped that publishing the fidelity protocol and findings for the AFFINITIE process evaluation will provide a methodological contribution to the fidelity literature that may inform future fidelity assessments in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for fidelity investigations. While the BCC fidelity framework provides a synthesised conceptualisation and definition of different fidelity dimensions, the authors themselves acknowledge that there is little standardised guidance on how to operationalise each dimension, and a consequent need for further empirical examples of how each dimension has been quantified and interpreted [14, 38]. It is thus hoped that publishing the fidelity protocol and findings for the AFFINITIE process evaluation will provide a methodological contribution to the fidelity literature that may inform future fidelity assessments in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Reach and adherence can impact on statistical power and interpretation of trial results, including under-estimating any efficacy. There is no consensus on the acceptable minimum adherence level in trials and no standardised approach to adherence measurement in the field of complex interventions [52]. A review of treatment adherence in public health research reported that only 27% of research checked adherence to protocol [53] and few prior sun protection intervention studies have assessed reach and adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Reach and adherence can impact on statistical power and interpretation of trial results, including underestimating any efficacy. There is no consensus on the acceptable minimum adherence level in trials and no standardised approach to adherence measurement in the field of complex interventions [53].…”
Section: Discussionmentioning
confidence: 99%